FEATURES OF CONSOLIDATED FINANCIAL STATEMENTS: FOREIGN EXPERIENCE - S. V. KUCHER (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article researches the features of preparation and submission of the consolidated financial statements of the world countries of different systems of accounting standardization in order to identify the areas of accounting improvement for the process of consolidation of financial reporting indicators. The main problems of consolidated financial statements preparation by business entities in Ukraine are determined. The author determines the theoretical and practical problems of consolidation of financial statements of organizational and methodical character. The comparative analysis of the features of standardization process of financial statements consolidation in the world countries is carried out. The main differences in the requirements for the formation of consolidated financial statements indicators of such countries as the French Republic, the Federal Republic of Germany, the Republic of Belarus and the People’s Republic of China are outlined. The main directions of scientific researches on the improvement of accounting and analytical support for the preparation of consolidated financial statements are formed.